2015
DOI: 10.1002/sia.5772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of layered titanate nanosheets using TOF‐SIMS and g‐ogram analysis

Abstract: The evaluation of nanostructure is important to develop the highly controlled nanomaterials. In this study, two kinds of layered titanate nanosheets, which were produced by using hexylamine and laurylamine, respectively, as surfactants were investigated by Gentle Secondary Ion Mass Spectrometry Gentle-SIMS (G-SIMS) and g-ogram, which is the latest Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) data analysis method for detecting more intact ions and obtaining the information on original chemical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The positive charged DDA molecules act as cations if the pH is adjusted to 10.0-11.0. Previous studies using Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) analysis, Gentle Secondary Ion Mass Spectrometry Gentle-SIMS (G-SIMS), and g-ogram methods also showed that the DDA molecule in only Ti DDA TEOA sample was not easily fragmented, implying the formation of robust hydrophobic domains with lamellar mesostructure 25), 26) . Thus, the proposed formation mechanism of layered titanate nanosheets is shown in Fig.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…The positive charged DDA molecules act as cations if the pH is adjusted to 10.0-11.0. Previous studies using Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) analysis, Gentle Secondary Ion Mass Spectrometry Gentle-SIMS (G-SIMS), and g-ogram methods also showed that the DDA molecule in only Ti DDA TEOA sample was not easily fragmented, implying the formation of robust hydrophobic domains with lamellar mesostructure 25), 26) . Thus, the proposed formation mechanism of layered titanate nanosheets is shown in Fig.…”
Section: Formation Mechanismmentioning
confidence: 99%